The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.4103/0971-4065.75220
|View full text |Cite
|
Sign up to set email alerts
|

Collapsing glomerulopathy in renal allograft biopsies: A study of nine cases

Abstract: Collapsing glomerulopathy (CG) is considered to be a distinct clinicopathologic pattern of proliferative podocyte injury. The clinical significance of CG in renal allograft biopsies is yet not clear due to the scant data on the occurrence of CG in renal transplant recipients. We identified nine cases of CG in allograft biopsies over a period of 2 years. Detailed clinical information, including follow-up data, was collected and histopathological analysis performed. All the nine patients were males with a mean a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 11 publications
2
13
2
Order By: Relevance
“…Most of the studies have reported that patients with CG eventually develop graft failure over a variable time period. [ 9 10 11 ] We also have observed that 11 (52.38%) out of 21 patients in our study developed graft failure over a period of 2.2 ± 1.7 years.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…Most of the studies have reported that patients with CG eventually develop graft failure over a variable time period. [ 9 10 11 ] We also have observed that 11 (52.38%) out of 21 patients in our study developed graft failure over a period of 2.2 ± 1.7 years.…”
Section: Discussionsupporting
confidence: 74%
“…[ 7 ] CG in renal allografts has been reported in literature in the form of few case reports and small studies [ Table 5 ]. [ 8 9 10 11 ] In the present study, the overall prevalence of CG in renal transplant was 0.83%. However, we report a higher prevalence of 1.4% in the last 4 years, which shows an increasing awareness of disease in recent years.…”
Section: Discussionsupporting
confidence: 43%
See 2 more Smart Citations
“…Neoplastic conditions like hemophagocytosis syndrome and multiple myeloma, drugs like interferon-α and bisphosphonates (pamidronate) can also lead to CG 17-20. Collapsing glomerulopathy has also been reported as de novo disease post renal transplant 21,22. Occasional genetic/ familial forms have been reported 23.…”
Section: Discussionmentioning
confidence: 99%